Dietary factors during early life program bone formation in female rats. Issue 1 (12th October 2016) - Chen, Jin‐Ran; Lazarenko, Oxana P.; Blackburn, Michael L.; Shankar, Kartik
Abstract : Nutritional status during intrauterine and early postnatal life impacts the risk of chronic diseases; however, evidence for an association between early‐life dietary factors and bone health in adults is limited. Soy protein isolate (SPI) may be one such dietary factor that promotes bone accretion during early life with persistent effects into adulthood. In the present study, we fed postnatal day (PND) 24 weanling female rats an SPI diet for 30 d [short‐term SPI (ST‐SPI)], and on PND 55, we switched SPI diet to control Cas diet until age ± mo. Rats then under went either ovariectomy (OVX) or sham surgery and there after either continued to be fed an SPI diet or control diet for 1 or 3 wk. We showed significantly increased bone mass in 30‐d SPI‐fed young rats compared with controls. OVX‐induced bone loss was associated with increased osteoblastic cell senescence. On the one hand, both long‐term SPI (continuous SPI diet throughout life) and ST‐SPI diet only in early life protected against 1 wk post–OVX‐associated bone loss. On the other hand, long‐term SPI diet diminished the loss of total, trabecular, and cortical bonemineral density, whereas ST‐SPI diet only reduced cortical bone mineral density loss 3wk post‐OVX. Persistent andprotective effects of SPIdietsonOVX‐inducedbone losswere associatedwithdown‐regulation of the caveolin‐1/p53‐mediated senescence pathway in bone. We recapitulated these results in cell cultures. Reprogramming of cellular senescence signaling by SPI‐associated isoflavones in osteoblastic cellsmay explain the persistent effects of SPI on bone. These results suggest thatOVX‐induced bone loss, in part, is a result of increased osteoblastic cell senescence, and that ST‐SPI diet early in life has modest but persistent programming effects on bone formation to preventOVX‐induced bone loss in adult female rats.—Chen, J.‐R., Lazarenko, O.P., Blackburn, M. L., Shankar, K. Dietary factors during early life program bone formation in female rats. FASEB J. 31, 376–387 (2017) www.fasebj.org